Determination of Liquidity Ratio: Analysis Before IPO and After IPO - Harry Pambudi (DINASTI RESEARCH, 2021)
Article Literature Review of Determinants of Company Liquidity Ratios related to the influence of Pre-IPO Conditions and Post-IPO Conditions is a scientific article to find out the phenomenon of influence between variables in further research related to the preparation of a hypothesis, within the scope of Financial Management. The preparation of this Literature Review article applies library research techniques, which are searched through Google Scholar, Mendeley and other academic online media. The issues raised in this article (Literature Review) are: 1) The effect of the condition of the company before the IPO on its liquidity ratio; 2) Effect of Company Conditions After IPO on Liquidity Ratio. Besides these two independent (exogenous) variables that influence the dependent variable (endogenous) Liquidity Ratio, other factors that can also be factors are Sales Growth, Earning per Share (EPS), and Ownership Structure.